1988
DOI: 10.1007/bf02279876
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia in Kawasaki disease: Follow-up study by cardiac catheterization and coronary angiography

Abstract: The clinical course of ischemic heart disease due to Kawasaki disease was analyzed. The subjects (children aged two months to eight years) were divided into two groups. Group 1 (n = 23) consisted of children who had sustained myocardial infarction (MI) and group 2 (n = 13) of those without clinical symptoms or signs of MI, but in whom signs of an obstructive lesion had appeared on coronary arteriography during the follow-up period. Changes in the left ventricular ejection fraction (LVEF) and the appearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…270 Myocardial dysfunction present shortly after MI can improve, although some patients will develop adverse ventricular remodeling and ventricular aneurysms if the damage is extensive. 271 Patients who have had an MI are at further risk of subsequent MI, although the risk is reduced with effective revascularization. Tsuda et al 272 reported long-term outcomes up to 33 years after surviving MI in 60 patients.…”
Section: Natural History and Cardiovascular Disease Eventsmentioning
confidence: 99%
“…270 Myocardial dysfunction present shortly after MI can improve, although some patients will develop adverse ventricular remodeling and ventricular aneurysms if the damage is extensive. 271 Patients who have had an MI are at further risk of subsequent MI, although the risk is reduced with effective revascularization. Tsuda et al 272 reported long-term outcomes up to 33 years after surviving MI in 60 patients.…”
Section: Natural History and Cardiovascular Disease Eventsmentioning
confidence: 99%
“…Indeed, it is rare to have symptoms of ischemic heart disease even in patients with severe obstructive lesions as a consequence of Kawasaki disease. 1 It is important, nonetheless, to identify those patients at risk. In this respect, most patients are too young to undergo exercise electrocardiography for evaluation of myocardial ischemia, and, even when they can be evaluated with exercise testing,' the sensitivity of this technique in diagnosing myocardial ischemia is very low.…”
mentioning
confidence: 99%
“…Peripheral vascular endothelial function also appears normal late after the acute illness irrespective of coronary artery involvement [95]. Kawasaki disease results in ischemic heart disease during short-to-midterm follow-up in 1–2% of patients [96]. Consequently, small numbers of children and adolescents have been treated by bypass grafting or by interventional catheter procedures.…”
Section: Resultsmentioning
confidence: 99%